Pengembangan Platform Coffee Shop KURLEB dengan Fokus pada User Interface dan Prinsip UX Law - Henoch Juli Christanto; Stephen Aprius Sutresno; Gilberto Dennis G E Sidabutar; Jesslyn Alvina Seah; Siemens Benyamin Tjhang; Yoel Krisrian (Journal of Information System Research (JOSH), 2023)
The increasing trend and public interest in coffee shops, also known as cafes. One of the cafes named Kopi KurangLebih has great potential to attract customers due to its strategic location, high-quality menu, and aesthetic ambiance. Although Kopi KurangLebih already has an Instagram account to showcase its content and engage with followers, the information provided is limited and lacks proper organization. Visitors to the coffee shop struggle to make menu choices due to the absence of a platform to display the available options. To address these challenges and improve the quality of service, a website is needed to document and present information that assists customers in making menu selections. The current reliance on social media as a source of information for coffee shops is inefficient and temporary, as the information shared only appears briefly on users' timelines. Hence, the development of an attractive and informative website for Kopi KurangLebih becomes necessary. The website should be designed according to user needs and the resources available to Kopi KurangLebih. By utilizing a digital information medium in the form of a website, potential customers can access and obtain information easily, thereby increasing their interest and purchasing power. The research also applies the Three Circles method and incorporates various UX Law principles into the user interface (UI) design. Through observations and analysis, the research identifies the values of Kopi KurangLebih, customer needs, and competitor values. This research successfully built a UI prototype of the KURLEB website, transforming it into an effective digital platform for promoting, storing, and providing information about Kopi KurangLebih. It also achieved a good user experience by providing relevant information, intuitive navigation, and appealing visual aesthetics. With a well-designed UI and the applied principles of UX Law, this website delivers a positive user experience, enhances customer engagement, and contributes to the sustainable marketing of Kopi KurangLebih as a local coffee shop brand.